Cardiac diagnostic work-up of ischaemic stroke. (21st May 2018) - Yang, Hayang; Nassif, Martina; Khairy, Paul; de Groot, Joris R; Roos, Yvo B W E M; de Winter, Robbert J; Mulder, Barbara J M; Bouma, Berto J
Abstract: Cardioembolic sources account for 20–30% of ischaemic strokes and are important to identify considering their prognostic and therapeutic implications. During the past years, new developments have been made in the cardiac diagnostic evaluation and management of patients with ischaemic stroke, especially regarding strokes of unknown aetiology. These recent advances have had a major impact on our understanding of embolic strokes, their diagnostic work-up, and clinical management. Herein, we propose a cardiac diagnostic work-up scheme for patients with ischaemic stroke from definite cardioembolic sources and embolic strokes of undetermined source.